Effectiveness and safety of intravesical Gentamicin therapy in patients with recurrent urinary tract infections caused by multidrug resistant organisms - Malik, Zubda (Journal of the Pakistan Medical Association, 2023)
A prospective study was conducted at the Liaquat National Hospital and Medical College, Karachi, to determine the effectiveness, feasibility, and safety of intravesical Gentamicin therapy among patients presenting with recurrent urinary tract infections (rUTIs). All patients aged 15 years, who presented with recurrent UTI, having 3 positive urine cultures, with neurogenic bladder, intermittent catheterisation, symptomatic UTIs, and multidrug resistant cultures, were included in the study. Data were compiled and analysed using SPSS version 26. An ethics committee approved the study. A total of 69 patients were enrolled. Most common organisms were Klebsiella (52.2percent), E. coli (27.5percent) and gram -ve bacilli (14.5percent). ---Continue